Analysis of Power complexity in existing algorithms against Ad-Hoc On demand Distance Vector Routing Protocol - Subramanian, K; Gnanakumaran, R (International Journal of Computer Sciences and Engineering, 2025)
The rapid evolution in the mobile communication field, the new alternatives is derived in which mobile devices form a self-creating, self-administering and self-organizing wireless networks. Mobile Ad Hoc Network (MANET) is one such arbitrary network in which all the nodes are mobile and consists of limited radio transmission range, battery power and channel bandwidth. These Mobile Ad Hoc networks are often used in emergency situations. The frequent change in topology leads to more consumption of energy, therefore saving power in such situations is of prime importance. In this paper compares some existing power consumption reducing algorithm.